Identificação e caracterização funcional de novas proteínas de grânulos densos de Neospora caninum - Torres, Jhoan David Aguillon (2024)
Neospora caninum is a protozoan that belongs to the Apicomplexa phylum , with a global distribution and serving as the etiological agent of neosporosis. Apicomplexan parasites require the formation of a parasita phorous vacuole (PV) for replication and maintenance of infection within the host. The formation of the PV depends on a coordinated protein secretion machinery from organelles such as micronemes, rhoptries, and dense granules. Dense granule proteins (GRAs) are essential for maintaining the structure of the PV, as they regulate its architecture, nutrient acquisition, and can modulate host gene expression and cell cycle. Little is known about the GRAs of N. caninum , which is why this study aimed to investigate the diversity and role of N. caninum GRAs to elucidate their biological functions and their role in parasite host interactions. Using in silico approaches, the diversity of these proteins was determined through comparative analyses with the model organism T. gondii . Subsequently, the BioID strategy was employed to confirm the predicted GRAs. To better understand the b iological role of specific GRAs, five proteins were studied using CRISPR/Cas9 technology, through endogenous tagging and gene knockout. Finally, genetically modified parasites deficient in the target GRAs were used to study their roles in parasitic replica tion, virulence modulation, and host immune response. A total of 145 GRAs were identified based on orthology with T. gondii , of which 81 were confirmed by BioID, validating their presence in N. caninum . The proteins GRA48, GRA62, GRA83, NSG1, and the hypot hetical protein NCLIV_001830 were selected for further analysis. All these proteins were localized in the PV. It was demonstrated that GRA48, GRA62, GRA83, and NCLIV_001830 are involved in parasitic replication. NCLIV_001830 was identified as a GRA that tr anslocates to the nucleus and, along with GRA62, is capable of regulating the expression of Nos2 and Nox2 . In BMDMs, except for GRA48, the GRAs were able to regulate the release of IL 12. In murine models, it was confirmed that the selected GRAs regulate p arasite virulence and are related to disease morbidity. It is concluded that N. caninum GRAs are a group of proteins essential for parasitic biology, crucial for parasite replication, host virulence, and immune response regulation. Therefore, understanding and further research on these proteins are essential for comprehending the parasite's biology and its relationship with the host, providing a foundation for developing prevention and prophylactic strategies for neosporosis.